The gendered effects of electoral institutions political engagement and participation - Kittilson, Miki Caul.; Schwindt-Bayer, Leslie A. (Oxford : Oxford University Press, 2013)
This volume argues that in most countries women continue to lag behind men in an array of political orientations and activities. Understanding this, and why some countries have been more successful than others in decreasing gender gaps, is imperative for producing stronger and more representative democracies.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Women political candidates; Women -- Political activity; Women legislators; Political participation -- Sex differences